MINAT PEMUDA PADA PERTANIAN HORTIKULTURA DI DESA KELOR KECAMATAN KARANGMOJO KABUPATEN GUNUNGKIDUL - Adriana Sharadhea Ningtyas; Bambang Santosa (Universitas Sebelas Maret (UNS), 2019)
Youth is a valuable asset to the country. The success of the nation's development depends on the level of its youth participation. Phenomena declining the interest of youth in agriculture is a special concern for society and government. Amid in the youth interest in the agricultural sector work, there is a group of farmers who have an interest in agriculture, especially horticultural. The purpose of this research is to see the process of increasing youth interest in horticultural farming, a factor that affects youth interest and the process of forming rational youth choices related to increased interest in horticultural farming. Qualitative research with a descriptive exploratory approach was conducted in the village Kelor Karangmojo District in Gunungkidul Regency. Sampling techniques using purposive sampling techniques. As for the research, informant consists of the youths who belong in a group of horticultural farmer Youth, non-village youth groups and village devices. Data is collected by observing, post conducting interviews and documentation. To test the data validity using source triangulation. Data analysis techniques use interactive models of Miles and Huberman with the rational choice theory of James S. Coleman.The results showed the process of increasing youth interest through: increased youth involvement in horticultural farms that are differentiated into direct involvement and supporting involvement about concerning frequency, long farmed and The youth-owned land area; Increased members of Horticulture Farmer Youth Group; Raising horticultural farmland; and increased youth innovations in horticultural farming. In the factors that affect the interest of the driving factor is the inner urge, social motivation, and emotional factor also the traction factor in the form of economic factors and market availability. The rational choice of youth against horticultural farming occurs because of the objectives that youths want to achieve by doing horticultural farming activities. Youth access to natural resources as well as capital is a tool for youth to get their goals. In maximizing the efforts of youth conduct collective behavior that is by forming a group of agriculture that has access to human resources and capital resources that can overcome the limitations of youth actors of individuals in activities Horticultural farming.